A new exact formulation and simulated annealing algorithm for one-sided closed loop layout - Niroomand, Sadegh; Mirzaei, Nima; Şahin, Ramazan; Vizvâri, Bêla (American Scientific Publishers order@aspbs.com, 2015)
A closed loop facility layout problem consists of an arrangement of several rectangular cells around a rectangular closed loop. This paper introduces a mathematical model for cases where the cells are located outside the closed loop. The transportation cost for a closed loop formation is proved to be strictly less than the transportation cost for a single row. A simulated annealing (SA) algorithm is used to solve benchmark problems in the single row facility layout literature. Latin square design is used to design experiments to find the most effective levels of factors for the SA algorithm. Computational results for the benchmark problems are strictly better for a closed loop formation than for single row formation. © © 2015 American Scientific Publishers.
Keywords: Close Loop Layout; Facility Layout; Mixed Integer Linear Programming; Simulated Annealing; Single Row Layout